Migalhas versus abundância de pão: por um lugar à mesa: uma interpretação feminista de Mt 15,21-28 - Sassi, Katia Rejane (2014)
This thesis proposes a feminist interpretation of Mt 15: 21-28. It investigates how the feminine character of the Canaanite woman is presented in the Christian interpretive history, in the Matthean community of the first century and in current days. From the perspective of the crumbs which fall from the table in confrontation with the bread in abundance , it aims to critically analyze the mechanisms of domination registered in the text and in the hermeneutic process, reconstructing it so that it can be the Good News of liberation and humanization for the men and women of all times. The first chapter presents a panoramic view of the reception and of the interpretation of this biblical text throughout the history of Christianity. It analyzes sermons and commentaries from the patristic and medieval periods, from the modern and post modern times,about the Canaanite woman, focusing mainly on the central content of the preaching and the woman s perspective. It seeks to reconstruct the path traced out by the text, revealing visions and ideologies which marked the androcentric reading of the different interpreters in different times and places. The second chapter elaborates an exegetical analysis, following some methodological steps which help in understanding the text. It seeks to gather a maximum amount of information based on the textual, literary, historical and theological analysis of the pericope, discovering the meaning and the message of life for the Matthean communities of the first century. The third chapter talks about a place at the table , reflecting and updating the text to our context in a feminist perspective. It explores the aspect of the border encounter, between Jesus and the woman, as a place of dialogue, of breaking barriers, of creating new relations and of a change in logic. It recovers the paradigm of the Canaanite as a model of liberation, of empowerment and of faith. It signals to a shared table as an inspiration and a challenge for the ekklesiaof Matthew and of the ecclesial communities of today, as well as for the life of the Canaanites of the XXI century.